2020
DOI: 10.3389/fpsyg.2020.01894
|View full text |Cite
|
Sign up to set email alerts
|

The Demands of Performance Generating Systems on Executive Functions: Effects and Mediating Processes

Abstract: Performance generating systems (PGS) are rule-and task-based approaches to improvisation on stage in theater, dance, and music. These systems require performers to draw on predefined source materials (texts, scores, memories) while working on complex tasks within limiting rules. An interdisciplinary research team at a large Western Canadian University hypothesized that learning to sustain this praxis over the duration of a performance places high demands on executive functions; demands that may improve the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…These findings to some extent corroborate past research results that posit that through interactive training professional actors can perform smoothly as their respective characters and concentrate on the communication with each other simultaneously ( Sun and Okada, 2021 ). Further, several possible explanations exist for the finding that professional actors showed an enhanced performance in the training sessions of our study; one would be their increased capacity for dual tasking, which is an executive function that has been shown to be improved by the practice of theater improvisation ( Hansen et al, 2020 ). Another would be professional actors’ superior capacities for perceiving the actions required of them due to them being good task performers, which is a reflection of the mirror neuron theory suggesting a similar mechanism for both the observation and execution of actions ( Calvo-Merino et al, 2005 ).…”
Section: Discussionmentioning
confidence: 92%
“…These findings to some extent corroborate past research results that posit that through interactive training professional actors can perform smoothly as their respective characters and concentrate on the communication with each other simultaneously ( Sun and Okada, 2021 ). Further, several possible explanations exist for the finding that professional actors showed an enhanced performance in the training sessions of our study; one would be their increased capacity for dual tasking, which is an executive function that has been shown to be improved by the practice of theater improvisation ( Hansen et al, 2020 ). Another would be professional actors’ superior capacities for perceiving the actions required of them due to them being good task performers, which is a reflection of the mirror neuron theory suggesting a similar mechanism for both the observation and execution of actions ( Calvo-Merino et al, 2005 ).…”
Section: Discussionmentioning
confidence: 92%
“…The partner developed, led, and delivered the dance intervention with dramaturgical and theoretical input from the research project leader. Based on Hansen’s previous research (e.g., Hansen et al, 2014 , 2020 ; Hansen, 2018a , b ) and the previously discussed theory, this input focussed on the safety of methods for sourcing dance creation in autobiographical memory, the exchange of such embodied memory, and the prioritization of creation and improvisation over demonstrating and teaching choreographed movement material. Quantitative and qualitative data were processed separately by two research team members with experience in the psychology of aging and education (Hartling) and artistic performance research (Main) who did not witness the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…The improved balance and mobility caused by dance practice ( Kshtriya et al, 2015 ) can positively affect the ability to partake in social and cultural offers out of the home. The maintenance of executive functions that dance improvisation has been found to affect ( Coubard et al, 2011 ; Hansen et al, 2020 ) may support the ability to overcome expectations of social barriers through problem solving and cognitive flexibility.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For instance, Zinelabidine et al (2022) reported increased EF (e.g., cognitive flexibility, resistance to interference on a Stroop set shifting tasks, and working memory) after an eight-week aerobic dance intervention in a group of school-age children compared to a control group (see also, Kattenstroth et al, 2013 for an example in older adults). Hansen et al (2020) hypothesized that greater performance demands, such as those required in dance, place a high demand on executive functions and may serve to improve these functions through practice. Accordingly, Hansen and colleagues highlighted how consistent performance requires a dynamic ability to shift attention, inhibit responses, and meet task demands with flexibility while remaining responsive to embodied and environmental input.…”
Section: Dance Experience As An Individual Differencementioning
confidence: 99%
“…Hansen et al (2020) hypothesized that greater performance demands, such as those required in dance, place a high demand on executive functions and may serve to improve these functions through practice. Accordingly, Hansen and colleagues highlighted how consistent performance requires a dynamic ability to shift attention, inhibit responses, and meet task demands with flexibility while remaining responsive to embodied and environmental input.…”
Section: Introductionmentioning
confidence: 99%